Necroptosis in cancer: An angel or a demon? - Tianzhen Wang; Yinji Jin; Weiwei Yang; Lei Zhang; Xiaoming Jin; Xi Liu; Yan He; Xiaobo Li (Tumor Biology)
In the past few decades, apoptosis has been regarded as the only form of programmed cell death. However, the traditional view has been challenged by the identification of several forms of regulated necrosis, including necroptosis. Necroptosis is typified by a necrotic cell death morphology and is controlled by RIP1, RIP3, and mixed lineage kinase domain–like protein. The physiological role of necroptosis is to serve as a “fail-safe” form of cell death for cells that fail to undergo apoptosis during embryonic development and disease defense. Currently, established studies have indicated that necroptosis is involved in cancer initiation and progression. Although elevated necroptosis contributes to cancer cell death, extensive cell death also increases the risk of proliferation and metastasis of the surviving cells by inducing the generation reactive oxygen species, activation of inflammation, and suppression of the immune response. Thus, questions regarding the overall impact of necroptosis on cancer remain open. In this review, we introduce the basic knowledge regarding necroptosis, summarize its dual effects on cancer progression, and analyze its advantages and disadvantages in clinical applications.